Consumer Culture and the Reinforcement of Social Class Distinctions in Post-Industrial Suburbs of Bandung - Hardiyanto, Feri (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2025)
This study investigates how suburban consumer culture in Bandung, Indonesia, reinforces social class distinctions, focusing on the interaction between material, symbolic, and infrastructural factors. With rapid urbanization and the rise of consumption-oriented middle classes, post-industrial suburban spaces have become key arenas for class performance. Using a mixed-methods approach, including quantitative surveys and qualitative interviews, data were collected from 400 residents of the Bandung Metropolitan Area (BMA). The research findings reveal that curated retail environments, such as lifestyle townships and regional malls, foster social class differentiation through access and affordability barriers, symbolically reinforcing middle- and upper-class exclusivity. Furthermore, the integration of digital platforms amplifies these distinctions, extending class signals into online spaces. The study underscores the importance of urban planning that incorporates social-mix impact assessments, affordable product lines, and inclusive community-based programming to mitigate exclusionary practices in suburban retail environments. The findings contribute to urban sociology by linking consumer spaces with class reproduction, offering practical insights for policymakers to address inequality in suburban areas.